2023
DOI: 10.15587/1729-4061.2023.285799
|View full text |Cite
|
Sign up to set email alerts
|

Development of the concept of building a corporate standard of portfolio management in the course of territory restoration planning in the context of Making-City project

Iurii Teslia,
Nataliia Yehorchenkova,
Oleksii Yehorchenkov
et al.

Abstract: It is shown that at the current stage, there is an important issue of creating portfolio management standards that could be successfully used for the post-war reconstruction of the territory of Ukraine. The object of research in this work is the process of restoration of the territory of Ukraine. The problem to be solved is the development of principles, processes, functions and models that underlie the portfolio management standard for territory restoration. Specific features of territory restoration projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…And this task is solved in this study. But just as in work [6], the task of devising a methodology for managing portfolios of projects that have a complex structure is not fully resolved. This is the aim of future research.…”
Section: Discussion Of Results Of Devising a Multiproject Approach To...mentioning
confidence: 99%
See 3 more Smart Citations
“…And this task is solved in this study. But just as in work [6], the task of devising a methodology for managing portfolios of projects that have a complex structure is not fully resolved. This is the aim of future research.…”
Section: Discussion Of Results Of Devising a Multiproject Approach To...mentioning
confidence: 99%
“…The peculiarity of our work is that it continues the research, the first part of which was reported in [6] and considered the creation of a portfolio management standard for territory restoration. As in work [6], the portfolios of projects for the restoration and/or development of territories are considered. These portfolios are created to facilitate the management of a strategic package of projects.…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Це важливо, щоб забезпечити виживання країни у довгостроковій перспективі, а також це дає надію та напрямок застосування зусиль уже сьогодні. Планування та підготовка сьогодні, заздалегідь, врятує життя та підвищить шанси на успіх [3].…”
Section: формування комплексного підходу до повоєнного складання ново...unclassified